Identification of polypharmacological anticancerous molecules against Aurora kinase family of proteins. Issue 4 (17th January 2022) - Gupta, Deepali; Kumar, Mukesh; Singh, Mandeep; Salman, Mohd; Das, Uddipan; Kaur, Punit
Abstract: The Human Aurora Kinase (AURK) protein family is the key player of cell cycle events including spindle assembly, kinetochore formation, chromosomal segregation, centrosome separation, microtubule dynamics, and cytokinesis. Their aberrant expression has been extensively linked with chromosomal instability in addition to derangement of multiple tumor suppressors and oncoprotein regulated pathways. Therefore, the AURK family of kinases is a promising target for the treatment of various types of cancer. Over the past few decades, several potential inhibitors of AURK proteins have been identified and have reached various phases of clinical trials. But very few molecules have currently crossed the safety criteria due to their various toxic side effects. In the present study, we have adopted a computational polypharmacological strategy and identified four novel molecules that can target all three AURKs. These molecules were further investigated for their binding stabilities at the ATP binding pocket using molecular dynamics based simulation studies. The molecules selected adopting a multipronged computational approach can be considered as potential AURKs inhibitors for cancer therapeutics.